2015
DOI: 10.1590/0102-311x00087514
|View full text |Cite
|
Sign up to set email alerts
|

Tipos de configuração familiar e condições de saúde física e psicológica em idosos

Abstract: Family configuration and physical and psychological health status in a sample of elderly Tipos de configuración familiar y condiciones de salud física y psicológica en ancianos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
18

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
(35 reference statements)
2
11
0
18
Order By: Relevance
“…Há ainda outro aspecto atualmente vivenciado por muitos pré-aposentados referente à independência financeira tardia dos filhos, o que pode postergar a aposentadoria, pois os primeiros permanecem os únicos provedores do lar (18) . Neste sentido, é oportuno ofertar aos trabalhadores informações acerca de economia doméstica, finanças e investimentos, estratégias para diminuírem os gastos e planejarem os recursos financeiros para a aposentadoria (19) .…”
Section: Discussionunclassified
“…Há ainda outro aspecto atualmente vivenciado por muitos pré-aposentados referente à independência financeira tardia dos filhos, o que pode postergar a aposentadoria, pois os primeiros permanecem os únicos provedores do lar (18) . Neste sentido, é oportuno ofertar aos trabalhadores informações acerca de economia doméstica, finanças e investimentos, estratégias para diminuírem os gastos e planejarem os recursos financeiros para a aposentadoria (19) .…”
Section: Discussionunclassified
“…It was found that elderly caregivers at the time of the study (one husband and three wives) were diagnosed with depression and anxiety, a fact that reveals frailty in the caregiver profile 27,28 . This reality of the elderly caregiver has become increasingly common and influences quality of life, acquired burden, as well as the changes resulting from aging [29][30][31] . With the stressors of this age group, it was found that the burden of the task of caring involves physical, psychological, social and financial problems.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, a média de idade de 54,8 anos, o fato de possuírem dependentes da renda familiar e estarem em algum tipo de relacionamento são características que se assemelham à atual estrutura das famílias brasileiras, nas quais os indivíduos pré-aposentados atuam como alicerces financeiros dos lares, sustentando seus descendentes, além de grande parte possuir cônjuge 20 .…”
Section: Discussionunclassified